Parental involvement in rural schools: A case study in Limpopo Province - Thulani Andrew Chauke; Nomazulu Ngozwana; Amohelang Machobane; Lepholletse Augusta Maria Maphuthi (International Review of Social Sciences Research, 2025)
The importance of parental involvement in children’s education cannot be overstated, as it enhances academic performance and the timely completion of studies. This study explores teachers’ perceptions of the involvement of parents in their children’s education in Greater Giyani in Limpopo Province, South Africa. Purposive sampling was employed to select four principals and nine teachers from four distinct schools participating in this qualitative study. Data were gathered through semi-structured interviews, and thematic analysis was used for data analysis. The findings reveal that teachers in rural Limpopo schools perceive parental involvement in two categories: supportive and partially supportive. Parents with formal education are actively engaged, attending meetings and assisting with schoolwork, while illiterate parents show lower levels of involvement. This study assumes significance in its contribution to the conceptualization and execution of pioneering programs aimed at enhancing parental involvement in schools situated in rural areas of Limpopo Province. The findings suggest that schools should establish targeted parental training programs and improve communication strategies to enhance parental involvement. Considering these results, the study recommends the formulation of clearer policies to guide both parents and teachers in school practices, fostering an environment that promotes the improvement of children’s performance in schools.